Successful use of a second course of caplacizumab in relapsed thrombotic thrombocytopenic purpura. (4th July 2022) - Shaffer, Jon; Grove, Angela
Abstract: There is limited data on the use of caplacizumab beyond the initial treatment course. We describe a patient case demonstrating the efficacy of a second course of caplacizumab in a patient with relapsed acquired thrombotic thrombocytopenic purpura (TTP). A 25-year-old female was treated for an initial event of TTP with steroids, plasma exchange, rituximab, and caplacizumab. Caplacizumab was continued 30 days post plasma exchange, which was on day 46 of treatment, at which time platelets had improved to 292 x 10 9 /L. Two weeks after completion of the first caplacizumab course, on day 60, she was readmitted with platelets of 5 x 10 9 /L. Daily plasma exchange and steroids were started on admission, with rituximab added on day 65. On day 67, the decision was made to re-initiate caplacizumab due to a platelet count of 21 x 10 9 /L. By day 72, platelets improved to 273 x 10 9 /L and the patient was able to be discharged and completed her second 30-day post plasma exchange course of caplacizumab without complications or further relapses.